Magnesium-based hydrogen storage composite material based on Ti-MOF and preparation method thereof
By introducing Ti-MOF additives, the micron-level refinement of the magnesium-based hydrogen storage material and the nano-level distribution of the catalyst are achieved, which solves the problem of agglomeration and growth of the material during the hydrogen absorption and release process, significantly improves the hydrogen storage performance, and obtains High-performance, long-cycle magnesium-based composite hydrogen storage system.
Patent Information
- Application Number
- CN202411648955.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-11-19
AI Technical Summary
The existing magnesium-based hydrogen storage materials have high temperature phase change during hydrogen absorption and discharge, resulting in material agglomeration and growth, reducing hydrogen storage performance, and the traditional catalyst distribution is uneven, and the synergistic catalysis effect is poor.
Using Ti-MOF as an additive, spherical Ti-MOF additives were prepared through the control of a mixed solvent of ethanol and toluene and tetrabutylammonium chloride surfactant, and were heat treated and ball milled in a protective atmosphere, and mixed with MgH2 powder. and processing to achieve micron-level refinement of materials and nano-level distribution of catalysts.
It effectively inhibits the agglomeration and growth of materials under high temperature conditions, improves the specific surface area and hydrogen absorption and release kinetic properties of magnesium-based materials, significantly improves hydrogen storage performance, and obtains micron-level high-performance and long-cycle magnesium-based composite storage. Hydrogen system.
Smart Images

Figure CN119160858B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hydrogen storage material preparation, and in particular to a Ti-MOF-based magnesium-based hydrogen storage composite material and a preparation method thereof. Background Art
[0002] As one of the most anticipated new energy sources in the 21st century, hydrogen energy has received more and more attention. Its application has many advantages, such as: the calorific value of hydrogen combustion reaches 142.351 kJ / kg, which is three times that of traditional gasoline, and its source is wide, the combustion product is pure water, and there is no pollutant emission. However, the efficient and safe storage technology of hydrogen is an urgent problem that restricts the rapid development of the hydrogen energy economy. At present, the industrial and laboratory hydrogen storage technology is mainly gaseous hydrogen storage in steel cylinders. The safety of hydrogen cylinders is poor, the volume hydrogen storage capacity is low, and the hydrogen storage capacity of steel cylinders is only 1 wt%, about 15 MPa. Liquid hydrogen storage needs to be maintained below the temperature of liquid nitrogen, consumes huge energy, and is expensive. It is mostly used in the aerospace field and has low actual civilian value.
[0003] Among the many hydrogen storage materials, various metal hydrides have broad application prospects as hydrogen storage materials. For example, the theoretical hydrogen storage capacity of magnesium-based hydrogen storage material MgH2 can reach 7.6 wt %, with excellent reversible hydrogen absorption and desorption performance, and can exist stably in the air. And as a common metal element, metal Mg is abundant in reserves and cheap. However, due to the stable thermodynamic properties of magnesium hydride material itself, the change of hydrogen absorption and desorption enthalpy = ±75 KJ / mol H2, and poor hydrogen absorption and desorption kinetics, its desorption temperature is above 350℃, which is not conducive to its practical application. In order to improve its thermal / kinetic properties, the method of refining material particles is first used to increase its specific surface area and improve the hydrogen diffusion rate in the hydrogen absorption and desorption reaction process. However, since the hydrogen absorption and desorption reaction is accompanied by a high-temperature phase transition above 300℃, the particles will significantly agglomerate and grow, thereby continuously deteriorating the hydrogen storage performance of the material. On the other hand, metals, oxides, halides, etc. are often added as catalysts to perform catalytic modification. The high-energy ball milling method of directly adding relevant metal catalysts results in uneven distribution of micron-level catalysts and poor synergistic catalytic effect. The chemical solvent reduction method is another similar existing technology that uses a strong reducing agent to perform co-precipitation reduction of Mg-based materials and catalysts in a specific organic solvent.
[0004] At present, mechanical ball milling is usually used for particle refinement in the preparation process of magnesium-based hydrogen storage materials. Ball milling to a few microns consumes a lot of energy and takes a long time to process. In addition, the existing technical solutions cannot introduce nano-catalytic metal clusters into magnesium-based hydrogen storage materials through simple and safe steps. In addition, micron-level materials are prone to agglomeration and growth under high temperature conditions during the preparation process, which greatly reduces the specific surface area of the material and seriously affects the material's hydrogen absorption and desorption kinetics. Summary of the invention
[0005] In view of the deficiencies of the above-mentioned prior art, the object of the present invention is to provide a magnesium-based hydrogen storage composite material based on Ti-MOF, and a preparation method and application thereof. The present invention introduces metal-organic framework materials as additives to efficiently achieve micron-level refinement of magnesium-based materials, nanoscale mixing and uniform distribution of surface catalytic metal clusters, and effective inhibition of micron-level material agglomeration growth under high temperature conditions. By introducing multifunctional MOF additives, the present invention takes various aspects into consideration and ultimately achieves the purpose of improving the hydrogen storage performance of magnesium-based materials.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0007] A method for preparing a magnesium-based hydrogen storage composite material based on Ti-MOF, comprising the following steps:
[0008] In a mixed solvent of ethanol and toluene, a transition metal source is used as a raw material and tetrabutylammonium chloride is used as a surfactant to obtain a mixed solution containing the transition metal source. An organic ligand, trimesic acid and a pH regulator are added to the mixed solution containing the transition metal source, and the mixture is reacted at room temperature to obtain a Ti-MOF additive.
[0009] Wherein, in the mixed solvent, the volume ratio of ethanol to toluene is 1:1.
[0010] Among them, the transition metal source can be selected from one of Ti, Co, Cu, Zn, Ag, La, Mn, Cr, Pt, Au, W, Cd, Pd, Mo, Ru, Rh, Nb, Zr, Y, Sc, V, Ce, Pr, Sm, Gd, and Nd.
[0011] The Ti-MOF white product is heat-treated under a protective atmosphere, ball-milled after the heat treatment, and then spherical MgH2 powder is added and ball-milled to obtain a mixed powder. Finally, the mixed powder is dehydrogenated and hydrogenated, and ball-milled to obtain a magnesium-based hydrogen storage composite material based on Ti-MOF.
[0012] The present invention uses a Ti source as a transition metal source, and obtains a spherical Ti-MOF additive by regulating the ratio of a mixed solvent of ethanol and toluene and the morphology of a tetrabutylammonium chloride surfactant. The Ti-MOF additive is heat-treated under a protective atmosphere, and then mixed with a spherical MgH2 powder to prepare a mixed powder. Finally, the mixed powder is dehydrogenated and hydrogenated to obtain a micron-sized magnesium-based hydrogen storage composite material based on the Ti-MOF-based additive. The present invention proposes a method that is simple, safe, and suitable for mass production of high-performance micron-sized magnesium-based hydrogen storage composite materials. By introducing Ti-MO F metal organic framework material is used as an additive to efficiently achieve micron-level refinement of magnesium-based materials, nano-level mixing and uniform distribution of surface catalytic metal clusters, and effective inhibition of agglomeration and growth of micron-level materials under high-temperature conditions. The present invention introduces a multifunctional Ti-MOF additive through a simple method, and simultaneously achieves its multiple functions of crushing agent, nanocatalyst, and agglomeration inhibitor, which respectively play a key modification role in the preparation particle size, catalytic efficiency, and long-cycle agglomeration inhibition stage of the material, and ultimately achieves the purpose of improving the hydrogen storage performance of magnesium-based materials, thereby obtaining a micron-level high-performance long-cycle magnesium-based composite hydrogen storage system.
[0013] In a preferred embodiment of the present invention, the usage ratio of tetrabutylammonium chloride to ethanol is 0.01 g~0.03 g:10 mL~30 mL.
[0014] In a preferred embodiment of the present invention, the ratio of the transition metal source to the mixed solvent of ethanol and toluene is 3 mmol:10 mL~50 mL.
[0015] In a preferred embodiment of the present invention, the usage ratio of trimesic acid to the mixed solvent of ethanol and toluene is 6mmol:200mL~2000mL.
[0016] In a preferred embodiment of the present invention, the mass percentage of the Ti-MOF in the magnesium-based hydrogen storage composite material is 1% to 30%.
[0017] In a preferred embodiment of the present invention, the heat treatment temperature is 500° C. and the holding time is 1 h to 4 h.
[0018] In a preferred embodiment of the present invention, the particle size of the MgH2 powder is 50 microns to 100 microns.
[0019] In a preferred embodiment of the present invention, the activation treatment method is: the mixed powder is kept at 140°C~160°C under vacuum for 3 h~5 h, then the temperature is increased to 400°C~600°C, and kept for 0.5 h~1.5 h until complete dehydrogenation, and then the pressure is maintained at 200°C~400°C and 2 MPa~4 MPa hydrogen pressure for 2 h~4 h until complete hydrogenation.
[0020] In a preferred embodiment of the present invention, the pH adjuster is KOH, and the pH of the mixed solution is adjusted to neutral.
[0021] Another object of the present invention is to provide a micron-sized magnesium-based hydrogen storage composite material based on a Ti-MOF-based additive obtained by any of the preparation methods described above, wherein the particle size of the magnesium-based hydrogen storage composite material is 0.5 microns to 3 microns.
[0022] Through preliminary research and exploration, it was found that the micron-scale magnesium-based hydrogen storage composite material prepared by ball-milling Ti-MOF and MgH2 powder mixed with Ti as the transition metal source in the present invention has better performance than magnesium-based hydrogen storage materials prepared with other transition metals such as Fe-MOF and Ni-MOF. The main reasons are: First, TiH2 / Ti second phase hydrogen storage phase is formed during the reaction of Ti-based MOF material, which further improves the rate of hydrogen absorption and desorption of the main phase of the magnesium-based material during the reaction. At the same time, it is found that the second phase hydrogen storage phase also has a certain hydrogen storage capacity. Secondly, the addition of Ti-MOF additives not only plays the role of a catalyst, but also plays the role of a crusher and agglomeration inhibitor. During the mixed ball milling preparation process of magnesium-based hydrogen storage materials based on Fe-MOF and Ni-MOF, the strong magnetism of Ni and Fe causes very serious adhesion, magnetic attraction and bonding agglomeration of the powders, which is not conducive to further small-particle preparation of the sample and dispersion during the reaction process. Therefore, the Ti-MOF non-magnetic additive of the present invention is proposed, which not only achieves a good particle size control effect during the ball milling process, but also the excellent catalytic performance of the Ti-based catalyst is fully exerted as the sample particle size decreases and the specific surface area increases, thereby obtaining a more excellent comprehensive hydrogen absorption and desorption performance.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The present invention uses Ti source as a transition metal source, and obtains a spherical Ti-MOF additive by regulating the ratio of ethanol and toluene in a mixed solvent of ethanol and toluene and regulating the morphology of a tetrabutylammonium chloride surfactant. The Ti-MOF additive is heat-treated under a protective atmosphere, and then mixed with a spherical MgH2 powder to prepare a mixed powder. Finally, the mixed powder is dehydrogenated and hydrogenated to obtain a micron-sized magnesium-based hydrogen storage composite material based on the Ti-MOF-based additive. The present invention proposes a simple, safe and suitable method for mass-producing high-performance micron-sized magnesium-based hydrogen storage composite materials. By introducing Ti The i-MOF metal organic framework material is used as an additive to efficiently achieve the micron-level refinement of magnesium-based materials, the nano-level mixing and uniform distribution of surface catalytic metal clusters, and the effective inhibition of the agglomeration and growth of micron-level materials under high-temperature conditions. The present invention introduces the multifunctional Ti-MOF additive through a simple method, and simultaneously realizes its multiple functions of crushing agent, nanocatalyst, and agglomeration inhibitor, which respectively play a key modification role in the preparation particle size, catalytic efficiency, and long-cycle agglomeration inhibition stage of the material, and ultimately achieves the purpose of improving the hydrogen storage performance of magnesium-based materials, thereby obtaining a micron-level high-performance long-cycle magnesium-based composite hydrogen storage system.
[0025] 2. Compared with pure MgH2 hydrogen storage materials, the Mg-TM MOF-H micron high-performance magnesium-based composite hydrogen storage material prepared by the present invention has a smaller reduction in hydrogen storage capacity and greatly improved kinetics. In addition, during the cycle, the material particle size is significantly reduced from 50 microns to 100 microns to 0.5 microns to 3 microns and the rapid hydrogen absorption and desorption reaction at this particle size is continuously maintained. Compared with the traditional MgH2 catalytic hydrogen storage material preparation process, the preparation process of the present invention is simple, the material nanocatalyst has good distribution, strong operability, short preparation cycle and high output rate. The required raw materials are cheap and easy to obtain, the preparation process cost is low and the safety is high, which is suitable for industrial low-energy consumption mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the SEM image of the Ti-MOF multifunctional additive prepared in the present invention.
[0027] Figure 2 XRD spectra of (1) Ti-MOF multifunctional additive, (2) Ti-MOF-MgH2 composite in ball milling state, (3) hydrogen absorption state and (4) dehydrogenation state prepared in the present invention.
[0028] Figure 3 The SEM morphologies of (1) MgH2 powder, (2) Ti-MOF-MgH2 composite after ball milling, and (3) to (5) hydrogenated Ti-MOF-MgH2 composite after 30 cycles of hydrogen absorption and desorption at different magnifications of the present invention.
[0029] Figure 4 The present invention shows (1) a bright field image of Ti-MOF-MgH2 micron-sized high-performance hydrogen storage particles, (2) diffraction rings, (3) and (4) high-resolution images at different magnifications, (5) a HAADF dark field image, and (6) and (7) EDS spectra of Mg and Ti elements.
[0030] Figure 5 This is a pressure-hydrogen storage capacity curve diagram of the Ti-MOF-MgH2 micron-sized high-performance hydrogen storage material of the present invention at different temperatures.
[0031] Figure 6 This is the fitting curve of the enthalpy change of hydrogen absorption and desorption reaction of the Ti-MOF-MgH2 micron-sized high-performance hydrogen storage material of the present invention.
[0032] Figure 7 This is the isothermal hydrogen absorption curve of the Ti-MOF-MgH2 micron-sized high-performance hydrogen storage material of the present invention at a series of temperatures.
[0033] Figure 8 This is the fitting curve of the hydrogen absorption activation energy of the Ti-MOF-MgH2 micron-sized high-performance hydrogen storage material of the present invention.
[0034] Fig. 9 DSC curves of the Ti-MOF-MgH2 micron-sized high-performance hydrogen storage material of the present invention at different heating rates.
[0035] Fig.10 The ln(β / T of the Ti-MOF-MgH2 micron-sized high-performance hydrogen storage material of the present invention is p 2 ) vs. 1000 / T p Fitting plot. DETAILED DESCRIPTION
[0036] The following is a detailed description of the technical solutions in the embodiments of the present invention in combination with the preferred embodiments and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] It should be noted that all professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.
[0038] Example 1
[0039] A method for preparing a Ti-MOF-MgH2 composite hydrogen storage material comprises the following steps:
[0040] (1) 0.569 g, 3 mmol TiCl4 was added to 30 mL of a mixed solvent of ethanol and toluene to form solution A. The specific morphology and structure of the product was regulated by adjusting the mixing ratio of ethanol and toluene. The volume ratio of ethanol to toluene in the mixed solvent was 1:1.
[0041] (2) Then, 0.02 g of tetrabutylammonium chloride surfactant was dissolved in 30 mL of ethanol and magnetically stirred at 800 rpm for 2 h to form solution B.
[0042] (3) Then, 0.996 g, 6 mmol of trimesic acid was added to a mixed solution of 200 mL of ethanol and toluene. The mixture was stirred magnetically at 800 rpm. At the same time, an appropriate amount of anhydrous KOH was added gradually. The pH value was adjusted to 7.0. At this time, the organic ligand was completely dissolved to form solution C.
[0043] (4) Solution B was then slowly added dropwise to solution A and magnetically stirred for 20 min until the reactants were completely mixed to form solution D. Solution D was placed in an ultrasonically stimulated stirring environment and then added dropwise to solution C. This process was accompanied by the generation of a white Ti-MOF product. This process was carried out with magnetic stirring at 600 rpm for 36 h. Finally, after the reaction precipitation was completed, the product was collected, washed with a mixed reagent of ethanol and toluene, centrifuged 5 times, and vacuum dried at 100 °C for 48 h before being stored in a glove box for later use.
[0044] (5) The obtained Ti-MOF material was heat treated at 500 °C in an argon atmosphere and kept warm for 2 h, pre-ball milled at 120 rpm for 2 h, and then spherical MgH2 powder material was added, wherein the mass percentage of Ti-MOF in the magnesium-based hydrogen storage composite material was 10%. Then, the mixture was ball milled at 400 rpm for 12 h. The mixture powder was then placed in a gas adsorption-desorption tester and kept warm at 150 °C for 4 h under vacuum. Then, the temperature was raised to 500 °C and kept warm for 1 h until complete dehydrogenation. Then, the mixture was kept at 300 °C and 3 MPa hydrogen pressure for 3 h until complete hydrogenation. Finally, the mixture was ball milled at 400 rpm for 8 h to form a Ti-MOF-MgH2 micron-level high-performance composite hydrogen storage material.
[0045] Example 2
[0046] A method for preparing a Ti-MOF-MgH2 composite hydrogen storage material comprises the following steps:
[0047] (1) 0.569 g, 3 mmol TiCl4 was added to 10 mL of a mixed solvent of ethanol and toluene to form solution A. The specific morphology and structure of the product was regulated by adjusting the mixing ratio of ethanol and toluene. The volume ratio of ethanol to toluene in the mixed solvent was 1:1.
[0048] (2) Then, 0.01 g of tetrabutylammonium chloride surfactant was dissolved in 10 mL of ethanol and magnetically stirred at 800 rpm for 2 h to form solution B.
[0049] (3) Then, 0.996 g, 6 mmol of trimesic acid was added to 1000 mL of a mixed solution of ethanol and toluene. The mixture was stirred magnetically at 800 rpm. At the same time, an appropriate amount of anhydrous KOH was gradually added. The pH value was adjusted to 7.0. At this time, the organic ligand was completely dissolved to form solution C.
[0050] (4) Solution B was then slowly added dropwise to solution A and magnetically stirred for 20 min until the reactants were completely mixed to form solution D. Solution D was placed in an ultrasonically stimulated stirring environment and then added dropwise to solution C. This process was accompanied by the generation of a white Ti-MOF product. This process was carried out with magnetic stirring at 600 rpm for 36 h. Finally, after the reaction precipitation was completed, the product was collected, washed with a mixed reagent of ethanol and toluene, centrifuged 5 times, and vacuum dried at 100 °C for 48 h before being stored in a glove box for later use.
[0051] (5) The obtained Ti-MOF material was heat treated at 500 °C in an argon atmosphere and kept warm for 2 h, pre-ball milled at 120 rpm for 2 h, and then spherical MgH2 powder material was added, wherein the mass percentage of Ti-MOF in the magnesium-based hydrogen storage composite material was 1%, and then ball milled at 400 rpm for 12 h. The mixed powder was then placed in a gas adsorption-desorption tester and kept warm at 140 °C for 3 h under vacuum, and then heated to 400 °C and kept warm for 0.5 h until complete dehydrogenation, and then kept at 200 °C and 2 MPa hydrogen pressure for 2 h until secondary hydrogenation, and then ball milled at 400 rpm for 8 h to finally form a Ti-MOF-MgH2 micron-level high-performance composite hydrogen storage material.
[0052] Example 3
[0053] A method for preparing a Ti-MOF-MgH2 composite hydrogen storage material comprises the following steps:
[0054] (1) 0.569 g, 3 mmol TiCl4 was added to 50 mL of a mixed solvent of ethanol and toluene to form solution A. The specific morphology and structure of the product was regulated by adjusting the mixing ratio of ethanol and toluene. The volume ratio of ethanol to toluene in the mixed solvent was 1:1.
[0055] (2) Then, 0.03 g of tetrabutylammonium chloride surfactant was dissolved in 25 mL of ethanol and magnetically stirred at 800 rpm for 2 h to form solution B.
[0056] (3) Then, 0.996 g, 6 mmol of trimesic acid was added to a 2000 mL mixed solution of ethanol and toluene. The mixture was stirred magnetically at 800 rpm. At the same time, an appropriate amount of anhydrous KOH was gradually added. The pH value was adjusted to 7.0. At this time, the organic ligand was completely dissolved to form solution C.
[0057] (4) Solution B was then slowly added dropwise to solution A and magnetically stirred for 20 min until the reactants were completely mixed to form solution D. Solution D was placed in an ultrasonically stimulated stirring environment and then added dropwise to solution C. This process was accompanied by the generation of a white Ti-MOF product. This process was carried out with magnetic stirring at 600 rpm for 36 h. Finally, after the reaction precipitation was completed, the product was collected, washed with a mixed reagent of ethanol and toluene, centrifuged 5 times, and vacuum dried at 100 °C for 48 h before being stored in a glove box for later use.
[0058] (5) The obtained Ti-MOF material was heat treated at 500 °C in an argon atmosphere and kept warm for 2 h, pre-ball milled at 120 rpm for 2 h, and then spherical MgH2 powder material was added, wherein the mass percentage of Ti-MOF in the magnesium-based hydrogen storage composite material was 30%. Then, the mixture was ball milled at 400 rpm for 12 h. The mixed powder was then placed in a gas adsorption-desorption tester and kept warm at 160 °C for 5 h under vacuum. Then, the temperature was raised to 600 °C and kept warm for 1.5 h until complete dehydrogenation. Then, the mixture was kept at 400 °C and 4 MPa hydrogen pressure for 4 h until secondary hydrogenation. Finally, the mixture was ball milled at 400 rpm for 8 h to form a Ti-MOF-MgH2 micron-level high-performance composite hydrogen storage material.
[0059] Results Analysis
[0060] Figure 1 This is the SEM image of the Ti-MOF multifunctional additive prepared by the present invention. Figure 1 It can be seen that due to the regulation of the ratio of ethanol to toluene and the morphology regulation of the tetrabutylammonium chloride surfactant, the present invention obtains a spherical Ti-MOF additive, which appears as a regular sphere with a diameter of about 3 microns.
[0061] Figure 2The XRD spectra of (1) Ti-MOF multifunctional additive, (2) Ti-MOF-MgH2 composite in ball-milled state, (3) hydrogen absorption state and (4) dehydrogenation state prepared by the present invention show that the Ti-MOF multifunctional additive synthesized by the present invention has good crystallinity. In addition to the diffraction peak of the parent phase MgH2 / Mg for hydrogen absorption and desorption in the composite, the presence of TiH2 and Ti are detected in the hydrogenated and dehydrogenated samples, respectively, proving the existence of the second phase hydride.
[0062] Figure 3 The SEM morphology images of (1) MgH2 powder, (2) Ti-MOF-MgH2 composite after ball milling, and (3) to (5) hydrogenated Ti-MOF-MgH2 composites at different magnifications after 30 cycles of hydrogen absorption and desorption of hydrogen in the present invention show that the MgH2 raw material is a regular sphere, and most of the particles are distributed in the range of 20 microns to 40 microns. During the preparation of the Ti-MOF-MgH2 micron-level high-performance hydrogen storage material, obvious cracking occurs. In the subsequent reaction process, the Ti-MOF additive acts as a particle crusher, which changes the brittleness of the magnesium hydride surface through contact with MgH2 during the ball milling process, significantly accelerating the ball milling crushing effect of the parent material, and finally obtaining micron-sized composite particles with uniform addition and coating. Figure 3 (3)-(5) show that with the formation of the new Mg / MgH phase in the high temperature hydrogen absorption and desorption cycle of the Ti-MOF-MgH2 composite at about 350°C, the composite particles show a phenomenon of transformation to irregular shapes, but compared with the raw material magnesium hydride, the particle size is significantly reduced to 1-2 microns, and the particle size remains in the micron size after 30 high temperature hydrogen absorption and desorption cycles. This phenomenon is mainly attributed to the introduction of the Ti-MOF multifunctional additive, in which the internal metal ion Ti generates the TiH2 / Ti catalytic system in situ, and a certain amount of oxygen in the organic acid ligand trimesic acid generates a thin MgO layer on the surface of the micron particles without significantly affecting the hydrogen storage capacity of the parent body. They act as agglomeration inhibitors, effectively inhibiting the agglomeration and growth of the micron composite particles under high temperature reaction conditions, so that the material always maintains excellent hydrogen storage kinetics for long cycles.
[0063] Figure 4 The present invention shows (1) a bright field image of Ti-MOF-MgH2 micron-sized high-performance hydrogen storage particles, (2) diffraction rings, (3) and (4) high-resolution images at different magnifications, (5) a HAADF dark field image, and (6) and (7) EDS spectra of Mg and Ti elements. The presence of the TiH2 phase can be confirmed by the diffraction rings and the high-resolution images, and the nanoscale uniform distribution of the Ti element on the substrate can be observed.
[0064] Figure 5The pressure-hydrogen storage capacity curve of the Ti-MOF-MgH2 micron-sized high-performance hydrogen storage material of the present invention at different temperatures shows that each hydrogen absorption and desorption platform is flat, the hysteresis of hydrogen absorption and desorption is reduced, and the neat system has excellent hydrogen absorption and desorption kinetics. The maximum reversible dehydrogenation capacity of the composite is 6.5 wt.%, indicating that the catalyst can still obtain a high hydrogen absorption and desorption capacity while fully improving the catalytic efficiency.
[0065] Figure 6 This is the fitting curve of the enthalpy change of hydrogen absorption and desorption reaction of the Ti-MOF-MgH2 micron-sized high-performance hydrogen storage material of the present invention. It can be seen that the formation enthalpy of the hydrogen absorption reaction of the system is -76.9±3.4 kJ / mol H2 and 77.4±2.8 kJ / mol H2.
[0066] Figure 7 This is the isothermal hydrogen absorption curve of the Ti-MOF-MgH2 micron-sized high-performance hydrogen storage material of the present invention at a series of temperatures. Figure 8 The hydrogen absorption activation energy fitting curve of the Ti-MOF-MgH2 micron-sized high-performance hydrogen storage material of the present invention is obtained by Figure 7 It can be seen that as the temperature decreases, the amount and rate of hydrogen absorption do not decrease significantly. This is mainly due to its fine particles and good catalytic efficiency, which improves the dissociation of reaction hydrogen molecules, the diffusion rate of hydrogen atoms in the bulk phase and the character of the new phase, thereby obtaining excellent hydrogen absorption kinetics. Figure 8 The fitting results show that the hydrogen absorption activation energy Ea of the complex is 49.6 ± 2.5 kJ / mol H2, which is significantly lower than that of pure magnesium 100.7 ± 5.2 kJ / mol H2.
[0067] Fig. 9 The DSC curves of the Ti-MOF-MgH2 micron-sized high-performance hydrogen storage material of the present invention at different heating rates are shown in FIG. Fig.10 The ln(β / T of the Ti-MOF-MgH2 micron-sized high-performance hydrogen storage material of the present invention is p 2 ) vs. 1000 / T p The fitting diagram is Fig. 9 It can be seen that the peak temperatures of the composite at heating rates of 10 K / min, 5 K / min and 3 K / min are measured to be 552.1, 537.6 and 524.8 K, respectively, and its dehydrogenation temperature is significantly lower than that of pure magnesium hydride. Fig.10 The Kissinger equation for ln(β / T p 2 )–1000 / T p The curve was fitted to obtain the activation energy E of the hydrogen release reaction of the Ti-MOF-MgH2 complex. dThe activation energy of hydrogen desorption is 97.3 ± 6.9 kJ / mol H2, which is significantly lower than the activation energy of hydrogen desorption reaction of pure MgH2, 181.4 ± 9.2 kJ / mol H2. From the DSC hydrogen desorption peak data and the hydrogen desorption activation energy data obtained by fitting, it can be seen that the hydrogen desorption kinetic rate of the Ti-MOF-MgH2 composite is significantly improved due to the introduction of the multifunctional Ti-MOF additive.
[0068] In summary, the present invention proposes a method that is simple, safe and suitable for mass production of high-performance micron-sized magnesium-based hydrogen storage composite materials: by introducing metal-organic framework materials as additives, the micron-sized refinement of magnesium-based materials, the nano-sized mixing and uniform distribution of surface catalytic metal clusters, and the effective inhibition of the agglomeration and growth of micron-sized materials under high-temperature conditions are efficiently achieved. The present invention introduces the multifunctional Ti-MOF additive by a simple method, and simultaneously realizes its multiple functions of crushing agent, nanocatalyst and agglomeration inhibitor, which respectively play a key modification role in the preparation particle size, catalytic efficiency and long-cycle agglomeration inhibition of the material, and finally achieves the purpose of improving the hydrogen storage performance of magnesium-based materials, thereby obtaining a micron-sized high-performance long-cycle magnesium-based composite hydrogen storage system.
[0069] It should be noted that when the present invention relates to a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundant description, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, once those skilled in the art know the basic creative concept, they can make other changes and modifications to these embodiments. Therefore, the attached protection scope is intended to be interpreted as including the preferred embodiment and all changes and modifications that fall within the scope of the present invention.
[0070] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the protection scope of the present invention and its equivalent technology, the present invention is also intended to include these changes and variations.
Claims
1. A method for preparing a magnesium-based hydrogen storage composite material based on Ti-MOF, characterized in that: The following steps are involved: In a mixed solvent of ethanol and toluene, a Ti source is used as a raw material and tetrabutylammonium chloride is used as a surfactant, and a mixed solution containing the Ti source is obtained. An organic ligand, trimesic acid, and a pH regulator are added to the mixed solution containing the Ti source, and the mixture is reacted at room temperature to obtain a Ti-MOF additive. Wherein, in the mixed solvent, the volume ratio of ethanol to toluene is 1:1; The Ti-MOF is heat-treated in a protective atmosphere, ball-milled after the heat treatment, and then spherical MgH2 powder is added and ball-milled to obtain a mixed powder. Finally, the mixed powder is activated to obtain a micron-sized magnesium-based hydrogen storage composite material based on the Ti-MOF additive.
2. The method for preparing the magnesium-based hydrogen storage composite material based on Ti-MOF according to claim 1, characterized in that: The dosage ratio of tetrabutylammonium chloride to ethanol is 0.01 g~0.03 g:10 mL~30 mL.
3. The method for preparing the magnesium-based hydrogen storage composite material based on Ti-MOF according to claim 1, characterized in that: The dosage ratio of Ti source to ethanol and toluene mixed solvent is 3 mmol:10 mL~50 mL.
4. The method for preparing the magnesium-based hydrogen storage composite material based on Ti-MOF according to claim 1, characterized in that: The dosage ratio of trimesic acid to the mixed solvent of ethanol and toluene is 6 mmol:200 mL~2000 mL.
5. The method for preparing the Ti-MOF-based magnesium-based hydrogen storage composite material according to claim 1, characterized in that: The mass percentage of the Ti-MOF in the magnesium-based hydrogen storage composite material is 1% to 30%.
6. The method for preparing the Ti-MOF-based magnesium-based hydrogen storage composite material according to claim 1, characterized in that: The heat treatment temperature is 500℃ and the holding time is 1 h~4 h.
7. The method for preparing the magnesium-based hydrogen storage composite material based on Ti-MOF according to claim 1, characterized in that: The particle size of the MgH2 powder is 50 microns to 100 microns.
8. The method for preparing the magnesium-based hydrogen storage composite material based on Ti-MOF according to claim 1, characterized in that: The activation treatment method is: keep the mixed powder at 140℃~160℃ under vacuum for 3 h~5 h, then increase the temperature to 400℃~600℃, keep it for 0.5 h~1.5 h until complete dehydrogenation, and then keep it at 200℃~400℃ and 2 MPa~4 MPa hydrogen pressure for 2 h~4 h until complete hydrogenation.
9. The method for preparing the magnesium-based hydrogen storage composite material based on Ti-MOF according to claim 1, characterized in that: The pH adjuster is KOH, which adjusts the pH of the mixed solution to neutral.
10. A Ti-MOF-based magnesium-based hydrogen storage composite material obtained by the preparation method according to any one of claims 1 to 9, wherein the particle size of the magnesium-based hydrogen storage composite material is 0.5 micrometer to 3 micrometers.
Citation Information
Patent Citations
Magnesium-based hydrogen storage composite material and preparation method thereof
CN103641066A
Preparation method for magnesium-based composite hydrogen storage material based on nano confinement of metal organic frameworks (MOFs) material
CN110526208A
Cited By
Preparation of hydrogen storage material and hydrogen storage method
CN121626932A